Gonococcal Conjunctivitis in a Low Birth Weight Baby with No Antenatal Care Visits: Case Report - Achmada Nadia Shobrina; Aty Firsiyanti (International Journal Labs, 2025)
Gonococcal conjunctivitis is a bacterial eye infection caused by Neisseria gonorrhoeae. This infection can occur in neonates or sexually active adults. Neisseria gonorrhoeae causes urogenital, rectal, pharyngeal infections, and hyperacute conjunctivitis. This bacterium can also invade the corneal epithelium, induce corneal stromal keratolysis, and corneal perforation. Gonococcal conjunctivitis usually presents with symptoms of severe mucopurulent conjunctivitis accompanied by eyelid edema, tenderness, and preauricular lymphadenopathy. This disease is usually associated with a Sexually Transmitted Disease (STD) but can also occur without genital infection. This case report is to report a case of gonococcal conjunctivitis in a neonate who has never had ANC, reviewed from the diagnosis and management of gonococcal conjunctivitis. By. a 20-day-old girl, to the pediatric clinic of Dr. Soegiri Lamongan complained of a swollen left eye accompanied by a large amount of yellow discharge for a week at home. Gonococcal conjunctivitis in neonates generally occurs due to direct transmission during delivery and exposure to infectious vaginal secretions. Antenatal care is crucial for maternal infection screening. Vertical transmission to the neonate can be prevented by administering antibiotics to the mother or applying antiseptic solutions to the baby's eyes immediately after birth. The diagnosis is based on history, physical examination, and supporting tests. This patient had a corneal ulcer complication, leading to a poor prognosis.